The cartulary of Newnham Priory. - Godber, Joyce (Publications of the Bedfordshire Historical Record Society, 1963)
The Cartulary of Newnham Priory A cartulary of the deeds and charters of Newnham Priory in Bedford was compiled in the early fifteenth century. It contains the Priory's deeds and charters from 1166 to 1409. The Latin transcriptions have been explained by brief explanatory headings in English for each of the 600 or more documents. The deeds are rich in field names for the places where the Priory held lands: Goldington, Biddenham, Cardington, Sharnbrook, Ravensden, Renhold, Stotfold and Wotton. The volume is in two parts. Part I includes a tribute In Memoriam to Frederick Joseph Manning.